2016
DOI: 10.1148/radiol.2016152038
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Integrity of Right Lateralized White Matter in Patients with Primary Insomnia: A Diffusion-Tensor Imaging Study

Abstract: Purpose To analyze the integrity of white matter (WM) tracts in primary insomnia patients and provide better characterization of abnormal WM integrity and its relationship with disease duration and clinical features of primary insomnia. Materials and Methods This prospective study was approved by the ethics committee of the Guangdong No. 2 Provincial People's Hospital. Tract-based spatial statistics were used to compare changes in diffusion parameters of WM tracts from 23 primary insomnia patients and 30 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
78
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 32 publications
9
78
4
Order By: Relevance
“…These investigators suggest that such reduced structural connectivity may represent a basis for reduced top-down control of negative emotions in GAD. Similarly, in PI, reduced FA has been reported in multiple white matter tracts, and reduced FA correlated with both PSQI and duration of PI (Li et al, 2016b). Hence GAD and PI may share disruption of axonal connectivity resulting in diminished top-down emotional regulation.…”
Section: Discussionmentioning
confidence: 81%
“…These investigators suggest that such reduced structural connectivity may represent a basis for reduced top-down control of negative emotions in GAD. Similarly, in PI, reduced FA has been reported in multiple white matter tracts, and reduced FA correlated with both PSQI and duration of PI (Li et al, 2016b). Hence GAD and PI may share disruption of axonal connectivity resulting in diminished top-down emotional regulation.…”
Section: Discussionmentioning
confidence: 81%
“…[3032] Zhu et al [21] reveal a significant increase in VMHC in the thalamus in 28 healthy participants after a total night of sleep deprivation. Li et al [18] find reduced fractional anisotropy in the thalamus, as well as negative correlation between fractional anisotropy in the thalamus and disease duration, in primary insomnia. Allen et al [33] find increased thalamic Gln plus Glu (Glx)/creatine/phosphocreatine (Cr) in patients with restless legs, which is correlated with the wake time during the sleep period.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has also been found that the gray matter density in the left inferior orbitofrontal cortex bordering the insula is negatively associated with earlier morning awakening in healthy subjects with insomnia symptoms, suggesting that the salience network may be related to the compromised ability to judge thermal comfort. [17] Using tract-based spatial statistics to analyze the integrity of white matter tracts, Li et al [18] observe that the fractional anisotropy in the thalamus and body corpus callosum is associated with the Pittsburgh Sleep Quality Index scores, supporting the notion that white matter tracts related to hyperarousal networks are affected in patients with primary insomnia. The above network abnormalities may in part be due to disruptions in the interhemispheric functional coordination communication between the bilateral cerebral hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression studies have shown that brain transcripts involved in myelin synthesis or maintenance are up‐regulated during sleep [Bellesi, ], with the proliferation of oligodendrocyte precursor cells doubling during sleep [Bellesi et al, ]. Diffusion tensor imaging (DTI) studies have documented reduced fractional anisotropy (FA) and increased radial diffusivity (RD) within fronto‐subcortical tracts in insomnia [Li et al, ; Spiegelhalder et al, ]. Although the relationship between DTI metrics is complex, a signature of reduced FA and increased RD can reflect microstructural changes associated with white matter degeneration, such as reduced axon density or reduced myelin [Zatorre et al, ].…”
Section: Introductionmentioning
confidence: 99%